2020
DOI: 10.1002/fee.2278
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing forest vulnerability and risk to climate‐change hazards

Abstract: Wildfires, drought, insect outbreaks, and windstorms are altering the forest‐associated ecosystem services that are essential for human well‐being, and the impacts of such events are likely to increase under ongoing climate change. However, a widely accepted and operational framework for evaluating forest vulnerability and risk to these disturbances remains lacking. We propose a general framework to assess forest vulnerability and risk based on the widely used concepts of exposure, hazard magnitude, susceptibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…Rigorous forest climate risk assessment is crucial for climate policies and programs relying on forest carbon uptake and storage, yet continental-scale risk assessment is currently lacking and urgently needed (21,27,28). Spatial quantification of risks can inform forest protocols in climate policy by ensuring that climate risks are adequately considered in program designfor example, through the construction of "buffer pools" and other insurance mechanismsand can guide forest project development and conservation (29).…”
Section: Main Textmentioning
confidence: 99%
“…Rigorous forest climate risk assessment is crucial for climate policies and programs relying on forest carbon uptake and storage, yet continental-scale risk assessment is currently lacking and urgently needed (21,27,28). Spatial quantification of risks can inform forest protocols in climate policy by ensuring that climate risks are adequately considered in program designfor example, through the construction of "buffer pools" and other insurance mechanismsand can guide forest project development and conservation (29).…”
Section: Main Textmentioning
confidence: 99%
“…Climate change-associated drought events are impacting forest ecosystem structure, function and distribution worldwide at a magnitude and speed unparalleled in human history (Allen et al 2015;Anderegg et al 2013a;Batllori et al 2020). In coming years, droughts are predicted to further increase in intensity and frequency in many parts of the world, including temperate regions (Gazol et al 2017;Lecina-Diaz et al 2021;Samaniego et al 2018). The capacity of many forest trees to persist in future environments will be determined by mechanisms that enable them to cope with recurrent and intense drought stress on a regular basis.…”
Section: Introductionmentioning
confidence: 99%
“…Research has suggested that various bat species, especially those with specific habitat and roosting requirements [ 39 , 74 ], like cavernicolous bats, are negatively affected by anthropogenically-induced landscape changes [ 4 , 15 , 35 , 42 , 43 ]. Most bat species are particularly sensitive to the loss of natural woody vegetation [ 6 ], land-cover types which are vulnerable to land-use change and fragmentation [ 43 , 47 ].…”
Section: Introductionmentioning
confidence: 99%